2015
DOI: 10.2298/mpns1506192r
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bilateral anterior cruciate ligament injuries

Abstract: Anterior cruciate ligament rupture of the contralateral knee most often occurs in young active athletes within the first four years after the initial reconstruction. Its frequency is not affected by sex, side of extremity, genetic predisposition, type of sport, concomitant injuries and the choice of graft. Returning to the same or higher level of sports activities after the first reconstruction is one of the preconditions for injuring the other knee in the same way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…2,3 Despite it being a wellestablished orthopaedic procedure, there is some concern that those who suffer an ACL tear will eventually require a contralateral reconstruction following their initial procedure. [4][5][6][7][8][9][10][11] With an incidence rate ranging from 2 to 14% (►Table 1), [5][6][7]10,12 contralateral injuries are quite concerning as they have been associated with poorer functional and patient-reported outcomes. 13 Some have reported that women and younger patients have a much higher risk of contralateral tears.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Despite it being a wellestablished orthopaedic procedure, there is some concern that those who suffer an ACL tear will eventually require a contralateral reconstruction following their initial procedure. [4][5][6][7][8][9][10][11] With an incidence rate ranging from 2 to 14% (►Table 1), [5][6][7]10,12 contralateral injuries are quite concerning as they have been associated with poorer functional and patient-reported outcomes. 13 Some have reported that women and younger patients have a much higher risk of contralateral tears.…”
mentioning
confidence: 99%
“…13 Some have reported that women and younger patients have a much higher risk of contralateral tears. 4,5 However, others have postulated that the activity performed while suffering the injury may be correlated with subsequent contralateral injury. 8 Contralateral ACL reconstructions can still result in satisfactory functional and patient-reported outcomes.…”
mentioning
confidence: 99%
“…The most common activities that cause these injuries are skiing, football, handball, basketball, volleyball and traffic accidents (up to 20%) [19]. Regarding the situation in which the injury occurred, our results show a deviation from the literature data, as 96.6% of our patients sustained sports injuries, most often during playing soccer [20,21].…”
Section: Discussionmentioning
confidence: 59%
“…The incidence of ACL injury has been increasing, and the most frequently injured are young, physically active persons [3][4][5][9][10][11][12][13]. Surgical reconstruction is the method of choice in the treatment of these injuries in recreational and professional athletes who have high levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%